Optimization of Aqueous Extraction Conditions of Inulin from the Arctium lappa L. Roots Using Ultrasonic Irradiation Frequency - Farzaneh Esmaeili; Mahnaz Hashemiravan; Mohammad Reza Eshaghi; Hassan Gandomi (Journal of Food Quality)
Ultrasound-assisted extraction is a promising technique to obtain active compounds from plants with high efficiency. The present study was conducted in two sections. In the first phase, the effect of solvent type (methanol, ethanol, water, and water-ethanol (50 : 50, v/v)) on inulin extraction yield from burdock roots (Arctium lappa L.) was investigated by the conventional method. The second phase aim was to optimize the condition of inulin and phenolic compounds including sonication time (10–40 min), sonication temperature (40–70°C), and solid/solvent ratio (1 : 20–1:40 g/ml) using response surface methodology (RSM). The results demonstrated that the highest inulin efficiency was extracted by water in the conventional method, which is equal to 10.32%. The optimum conditions of ultrasound-assisted water extraction for independent variables including sonication time and temperature as well as solid/water ratio were 36.65 min, 55.48°C, and 1 : 35 g/ml, respectively, which were determined on the maximization of inulin and total phenol content and minimization of IC50. At this optimum condition, inulin yield, phenolic compounds, and IC50 were found to be 12.46%, 18.85 mg GA/g DW, and 549.85 µg/ml, respectively. Regarding the results of this research, ultrasound-assisted extraction can be used as an alternative to the conventional extraction methods in extracting bioactive compounds from medicinal plants because it may improve the mass transfer, reducing the extraction time and the solvent used.